Answer:
If [tex]p\ge -\dfrac{1}{3},[/tex] then [tex]x>\dfrac{2}{3}+p[/tex] and [tex]mn=\dfrac{2}{3}+p=\left(\dfrac{2}{3}+p\right)\cdot 1,\ \ m+n=\dfrac{5}{3}+p[/tex]
Step-by-step explanation:
Solve two inequalities for x.
1. [tex]2,018x-p<2,020x+p[/tex]
Separate terms with x and without x into two sides:
[tex]2,018x-2,020x<p+p\\ \\-2x<2p[/tex]
Multiply by -1:
[tex]2x>-2p\\ \\x>-p[/tex]
2. [tex]7x+3p<10x-2[/tex]
Separate terms with x and without x into two sides:
[tex]7x-10x<-2-3p\\ \\-3x<-2-3p[/tex]
Multiply by -1:
[tex]3x>2+3p\\ \\x>\dfrac{2}{3}+p[/tex]
Find the largest set of x values satisfying both inequalities:
[tex]x>-p\\ \\x>\dfrac{2}{3}+p[/tex]
If
[tex]-p>\dfrac{2}{3}+p\\ \\-2p>\dfrac{2}{3}\\ \\2p<-\dfrac{2}{3}\\ \\p<-\dfrac{1}{3},[/tex]
then [tex]x>-p[/tex] and [tex]mn=-p=p\cdot (-1),\ m+n=p-1.[/tex] In this case both m and n are negative.
If [tex]p>-\dfrac{1}{3},[/tex] then [tex]x>\dfrac{2}{3}+p[/tex] and [tex]mn=\dfrac{2}{3}+p=\left(\dfrac{2}{3}+p\right)\cdot 1,\ \ m+n=\dfrac{5}{3}+p[/tex]
If [tex]p=-\dfrac{1}{3},[/tex] then [tex]x>\dfrac{1}{3}[/tex] and [tex]mn=\dfrac{1}{3}=\dfrac{1}{3}\cdot 1,\ \ m+n=\dfrac{4}{3}[/tex]